(untitled) (Altre Modernità, 2017)
The literature of Jorge Luis Borges is characterized by being based on literary traditions of other latitudes. "Secondhand" literature questioned his detractors. From the literary resources implemented by this author - translation, copying, plagiarism as "duty" and "pleasure" would be considered the various literary artifices of transfiction in some Argentine writers of SXX and SXXI as Fogwill; Martin Kohan; Sylvia Molloy and Juan José Saer.